Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Prilaku Peserta Didik Keles VIII di SMP N 6 Lubuk Basung - Efni Lestarida; Fenny Ayu Monia; Mardiati M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The influence of Islamic religious education students on the behavior of class VIII students in junior high school N 6 Lubuk Basung. This research is motivated by various problems of children aged junior high schools who behave or act inappropriately as students or students, because students often act impolitely and skip school, are lazy about studying and so forth. The problem revealed in this research is how The influence of Islamic religious education learning has an impact on students behave well and politely as expected. good behavior towards yourself and in social behavior. So that students can behave better with carry out all the commandments of Allah and stay away from all his prohibitions, respect parents, teachers and fellow friends. As the main task of Islamic religious education is to help coaching students in piety and good morals. Educational learning Islam influences the formation of students' personalities, because students are expected to will behave noblely, namely respecting parents and teachers and respecting friends. So that achieving educational goals to form a generation that is complete and has intelligence intellectual, good attitude with the skills needed to carry it out life.